A cautionary note on the potential pitfalls of using N-terminal truncated CD63 to label small extracellular vesicles - Elias Sulaiman; Derek M. Yellon; Sean M. Davidson (Scientific Reports)
Abstract Small extracellular vesicles (sEV) are nanosized vesicles that facilitate intracellular communication. A significant research obstacle is the isolation of sEV devoid of non-sEV contaminants. Immunoaffinity capture with sEV-specific antibodies is an attractive approach to purifying sEV, but it risks disrupting the vesicles during antibody dissociation. Furthermore, immunoaffinity capture may require the modification of EV-specific proteins for the incorporation of tags on the EV surface, with unknown implications on EV production and function. The aim of this study was to investigate whether a previously reported CD63 truncation is efficient for the incorporation of small tags on the extravesicular surface. We therefore conjugated ALFA-tag to N-terminal-truncated CD63, and included nanoluciferase at the C-terminus, for luminescent tracing of the sEV. Full-length CD63-nanoluciferase was used as a control. Plasmid constructs expressing these proteins were transfected into HEK293 cells. In contrast to a previous report, the N-terminal truncation of CD63 impaired its membrane localisation and reduced the yield of EVs. Further investigation revealed that some of the tagged CD63 was co-localized with aggresomes and was preferentially secreted from the cells as soluble protein rather than being associated with sEV. These results demonstrate that CD63 truncation can impair its function and EV yield, potentially generating misleading results.